Peningkatan Daya Saing UMKM Ibu Imas Melalui Sosialisasi Strategi Branding dan Digital Marketing Berbasis Media Sosial di Desa Mandalare - Andifa Dwi Fani; Ai Nurul Walidah; Rendi Herdiana; Tintin Sri Agustin (Khidmat, 2025)
MSMEs are a vital pillar of the Indonesian economy, including in Mandalare Village. However, most MSMEs still face challenges in digital marketing and strengthening their brand identity. This issue is also experienced by Mrs. Imas, the owner of a traditional snack business in Taringgul Hamlet. This community service activity aims to improve the competitiveness of Mrs. Imas's MSME through socialization of branding strategies and social media-based digital marketing. The method used was Participatory Action Research (PAR), with a participatory approach through observation, interviews, mentoring, and training. The activity was conducted over a one-month period with four meetings. The results showed an increase in MSME understanding of the importance of brand identity and digital promotion. Dapur Snack Bu Imas successfully established a business logo, packaging labels, and nameplates as business identities. Furthermore, product promotions began to be implemented through social media platforms like WhatsApp, utilizing the digital menu designs she had created. Through this program, Mrs. Imas's MSME was able to build a basic brand and begin adapting to digital marketing, thus expanding its product reach and potentially increasing its competitiveness.